PENDEKATAN PEMBELAJARAN DAN TINGKAT USIA MENINGKATKAN KETERAMPILAN BERMAIN SEPAKBOLA - Waluyo, Waluyo (Jurnal Phederal Penjas, 2008)
The main purpose of this reaserch was to examine deference of the effect of learning approach and age level to an efficient and effective soccer playing skill which is suitable for children's acceleration of development stages, is needed. The outcome of such research is applicable for the soccer skill learning for children at the school age level or at football schools. The research employs the experimental method with 2 x 2 factorial design. Fourthy male students of elementary school taken by purposive random sampling, were classified into four cells. Data of soccer skill are taken the MorChristian General Soccer Ability Skill